ETHICS, CORPORATE SOCIAL RESPONSIBILITY AND THE USE OF ADVISORY SERVICES PROVIDED BY SMEs: LESSONS LEARNT FROM JAPAN - Hasnah Haron,; Ishak Ismail,; Sobei Oda, (Asian Academy of Management Journal, 2015)
Japan has a high-income economy and a high Consumer Price (CPI) index. Because Malaysia desires to have a high-income economy, it has much to learn from SMEs in Japan, which have proven successful. A study was conducted on 17 SMEs in Japan. Data were collected by sending a set of questions to respondents and by interviewing them using the same set of questions if they are willing to be interviewed. Interviews were also conducted at three large companies that were once SMEs. The results indicated that SMEs in Japan emphasise seniority and treat their business like a family. SMEs in Japan value customer satisfaction do not believe in "quick wins" and ensure that the business is expanded progressively, not abruptly. They also believe that it is their responsibility to preserve traditional culture. The challenges that they faced included declines in sales due to the decline in foreign visits to Japan and the decreased demand for traditional products. An additional factor contributing to the success of SMEs in Japan is the Japanese government's ability to "make the blue collars' conditions equal to the white collars conditions'", particularly through the expanded application of the monthly payment, lifetime employment and seniority-based payment and promotion systems in SMEs, making them resemble large corporations. The factors that contribute to the success of Japanese SMEs can be emulated in Malaysia.